2003
DOI: 10.1007/bf02294732
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the Identifiability of Thurstonian Paired Comparison Models Under Multiple Judgment

Abstract: Thurstonian paired comparison models, identifiability, multiple judgment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…will be equivalent to the estimated model (Tsai, 2003, Corollary 1). In Equation 24, c is a positive constant, and d is an n ϫ 1 vector of constants.…”
Section: Equivalent Covariance Structures and Model Interpretationmentioning
confidence: 97%
“…will be equivalent to the estimated model (Tsai, 2003, Corollary 1). In Equation 24, c is a positive constant, and d is an n ϫ 1 vector of constants.…”
Section: Equivalent Covariance Structures and Model Interpretationmentioning
confidence: 97%
“…For example, ThurstoneÕs ''Case 5'' postulates that all stimuli are judged independently of each other with equal stimulus variances. Tsai (2000Tsai ( , 2003 showed that the ''Case 5'' hypothesis cannot be tested uniquely for ranking or paired comparison data since an infinite number of different stimulus-covariance matrices yield the same predictions as the identity matrix conjectured under ''Case 5''. In contrast, the hypothesis that all stimuli are equally distant to each other (i.e., they exhibit the same similarity relations) is unique and testable.…”
Section: Discussionmentioning
confidence: 94%
“…However, other decompositions may be possible as well that may prove equally useful in understanding evaluative processes. In view of the under-parameterization of R B , it is also important to study the equivalence classes for the proposed decomposition of R B that yield the same fit but are based on a different covariance structure (Tsai, 2003). Such an analysis is valuable to improve our understanding of how to interpret a particular covariance structure under consideration.…”
Section: Discussionmentioning
confidence: 98%